Institutional Arrangements for Macroprudential Policy in Asia - Lim, Cheng (IMF Working Papers; Working Paper ;, 2013)
This paper surveys institutional arrangements for macroprudential policy in Asia. Central banks in Asia typically have a financial stability mandate, and play a key role in the macroprudential framework. Smaller and more open economies with prudential regulation inside the central bank tend to have institutional arrangements that give the central bank a leading role. In larger and more complex economies where prudential regulation is outside the central bank, the financial stability mandate is usually shared with other agencies and the government tends to play a leading role. Domestic policy coordination is typically performed by a financial stability committee/other coordination body while cross-border cooperation is largely governed by Memoranda of Understanding.